LncRNA BC032020 suppresses the survival of human pancreatic ductal adenocarcinoma cells by targeting ZNF451 - Zhang, Zhipeng (Int J Oncol, 2018)
This study examined the effects of long non-coding RNA (lncRNA) BC032020 on the development of human pancreatic ductal adenocarcinoma (PDAC), and the potential molecular mechanisms responsible for these effects. The expression of BC032020 was assessed in 20 pairs of PDAC tumor tissues and adjacent normal tissues. The overexpression of BC032020 was enforced in the AsPC-1 and PANC-1 cells, and the effects on cell proliferation, cell cycle distribution, cell migration and apoptosis were determined. We also analyzed the functions of zinc finger protein 451 (ZNF451), which shares a gene sequence with two exons of BC032020 and a non-coding region with another two exons, in PDAC cells. The AsPC-1 and PANC-1 cells that overexpressed BC032020 were used to establish a subcutaneous tumor xenograft model in order to examine the effects of BC032020 on tumor growth in vivo. The results revealed that the BC032020 levels in the PDAC tumor tissues were lower than those in the adjacent normal tissues, and ZNF451 expression inversely correlated with the BC032020 levels in the PDAC tumor tissues and cell lines. BC032020 overexpression led to a decrease in ZNF451 expression; it also suppressed the proliferation and migration of the AsPC-1 and PANC-1 cells, and induced G1 phase arrest and cell apoptosis. The results of in vivo experiments revealed that BC032020 suppressed tumor growth in a xenograft model by inhibiting ZNF451 expression. Taken together, the findings of this study indicate that BC032020 suppresses the survival of PDAC cells by inhibiting ZNF451 expression.